Peran Inkubator Bisnis Rumah Berdaya Cilegon dalam Meningkatkan Kapasitas UMKM - M Ripa'i Apriansyah; Gian Nova Sudrajat Nur; Sumintak Sumintak (Lembaga Teewan Journal Solutions, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, yet they continue to face constraints in production capacity, legality, and marketing. The presence of business incubators such as Rumah BerdayaCilegon (RBC) is vital to address these challenges. This study aimed to examine in depth the programs, implementation processes, roles, and impacts of RBC in enhancing MSME capacity in Cilegon City. A descriptive qualitative method was employed. Data were collected through participatory observation, unstructured in-depth interviews with RBC’s Chief Executive Officer and five assisted MSME actors, and document study. Data analysis was carried out interactively through three stages: data reduction, data display, and conclusion drawing. The results reveal that RBC runs four core programs: the Free Halal Certification for 1,000 MSMEs, Packaging Facilitation for 100 MSMEs, Production Capacity Enhancement Assistance, and an Entrepreneurship Incubation Program. All programs are implemented through integrated educative, facilitative, representative, and technical roles. The programs have proven effective in improving product quality, production efficiency, business legality, packaging competitiveness, and market access for MSMEs. The impacts include increased income, job creation, a shift towards an entrepreneurial mindset, strengthened community solidarity, and the establishment of cross-sector institutional partnerships. Hence, RBC plays a strategic role as a participatory and sustainable agent of MSME-based community economic empowerment.